Measuring cortisol in serum, urine and saliva – are our assays good enough?. (May 2017) - El-Farhan, Nadia; Rees, D Aled; Evans, Carol
Cortisol is a steroid hormone produced in response to stress. It is essential for maintaining health and wellbeing and leads to significant morbidity when deficient or present in excess. It is lipophilic and is transported bound to cortisol-binding globulin (CBG) and albumin; a small fraction (∼10%) of total serum cortisol is unbound and biologically active. Serum cortisol assays measure total cortisol and their results can be misleading in patients with altered serum protein concentrations. Automated immunoassays are used to measure cortisol but lack specificity and show significant inter-assay differences. Liquid chromatography – tandem mass spectrometry (LC-MS/MS) offers improved specificity and sensitivity; however, cortisol cut-offs used in the short Synacthen and Dexamethasone suppression tests are yet to be validated for these assays. Urine free cortisol is used to screen for Cushing's syndrome. Unbound cortisol is excreted unchanged in the urine and 24-h urine free cortisol correlates well with mean serum-free cortisol in conditions of cortisol excess. Urine free cortisol is measured predominantly by immunoassay or LC-MS/MS. Salivary cortisol also reflects changes in unbound serum cortisol and offers a reliable alternative to measuring free cortisol in serum. LC-MS/MS is the method of choice for measuring salivary cortisol; however, its use is limited by the lack of a single, validated reference range and poorly standardized assays. This review examines the methods available for measuring cortisol in serum, urine and saliva, explores cortisol in disease and considers the difficulties of measuring cortisol in acutely unwell patients and in neonates.